The Effect of Price on The Diversity of Products on Purchase Decisions - Ayu Pipit Nurhayati (Program Studi Manajemen, Fakultas Ekonomi, Universitas Langlangbuana, 2020)
Leather shoes are shoes that in modern times are not only used for formal events, but these time leather shoes are also used as a trend of modern shoes that can be worn at any time, such as college, hang out or work. The amount of creativity of young people who are ready to take risks to increase the trend of leather shoes by creating various types of businesses, from many businesses, one of which is Portee Goods. This study aims to empirically examine the effect of price and product diversity on purchasing decisions for leather shoes at Portee Goods. The sample used in this study is online consumers who buy oxford-type leather shoes who are male also have their own income or are in working status. This sample is done using the Non-Probability Sampling method. Data collection was carried out using a questionnaire distributed as many as 88 questionnaires. The statistical method uses path analysis (Path Analysis), by testing the hypothesis of the parsial statistical test (t-test) and simultaneous (f test). The results of this study indicate that price and product diversity significantly influence the purchasing decision of oxford type leather shoes at Portee Goods.